The synergistic role of gut microbiota and RNA in metabolic diseases: mechanisms and therapeutic insights - Huang, Zhuo; Yao, Qinyan; Ma, Shuang; Zhou, Jinjie; Wang, Xiaoxuan; Meng, Qingguo; Liu, Yaxin; Yu, Zihan; Chen, Xin (Frontiers in Microbiology, 2025)
The gut microbiota plays a pivotal role in human metabolic health by influencing immune responses, digestion, and metabolic homeostasis. Recent research highlights the intricate interactions between gut microbiota and RNA, especially non-coding RNAs, in regulating metabolic processes. Dysbiosis of the gut microbiota has been linked to metabolic disorders such as type 2 diabetes, obesity, metabolic-associated fatty liver disease (MAFLD) and metabolic heart disease. Microbial metabolites, including short-chain fatty acids (SCFAs), modulate RNA expression, influencing lipid metabolism, glucose regulation, and inflammatory responses. Additionally, microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) serve as critical regulators in these processes, with emerging evidence showing that gut-derived metabolites affect post-transcriptional gene regulation. This review synthesizes the current understanding of the gut microbiota-RNA axis and its role in metabolic diseases. By exploring the molecular mechanisms, particularly how gut microbiota-derived signals modulate RNA pathways, the review underscores the potential of targeting this axis for therapeutic interventions. Furthermore, it examines how dysbiosis leads to epigenetic changes such as m6A RNA methylation, contributing to disease pathogenesis. These insights offer a new perspective on the prevention and treatment of metabolic diseases, with potential applications in personalized medicine.